2023
DOI: 10.1021/acs.analchem.3c01151
|View full text |Cite
|
Sign up to set email alerts
|

Quantification of Polymer Surface Degradation Using Fluorescence Spectroscopy

Abstract: One solution to minimizing plastic pollution is to improve reuse and recycling strategies. Recycling, however, is limited by the overall degradation of plastics being used, and current techniques for monitoring this plastic degradation fail to observe this in its early stages, which is key for optimizing reusability. This research seeks to develop an inexpensive, reproducible, and nondestructive technique for monitoring degradation of polyethylene (PE) and polypropylene (PP) materials using Nile red as a fluor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

2
1

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 59 publications
(122 reference statements)
0
4
0
Order By: Relevance
“…Fit data were used to ascertain fluorescence peak location shift information. Center of mass data (COM) were calculated using both fit data and raw data with no deviation in COM calculations for any of the data sets reported . Second derivative analysis was independently performed on postcollect data smoothed with a sixth order Saviztky-Golay (SG) filter with data initially smoothed followed by a sequential numerical gradient.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Fit data were used to ascertain fluorescence peak location shift information. Center of mass data (COM) were calculated using both fit data and raw data with no deviation in COM calculations for any of the data sets reported . Second derivative analysis was independently performed on postcollect data smoothed with a sixth order Saviztky-Golay (SG) filter with data initially smoothed followed by a sequential numerical gradient.…”
Section: Methodsmentioning
confidence: 99%
“…Center of mass data (COM) were calculated using both fit data and raw data with no deviation in COM calculations for any of the data sets reported. 46 Second derivative analysis was independently performed on postcollect data smoothed with a sixth order Saviztky-Golay (SG) filter with data initially smoothed followed by a sequential numerical gradient. SG and 2-Gaussian filter results were compared and showed no significant deviation between techniques.…”
Section: Methodsmentioning
confidence: 99%
“…By comparing the size of the angle at the moment of contact, it is possible to understand the wettability of the material in the medium [30,31]. The larger the contact angle, the weaker the wettability [32].…”
Section: Capacity Of Wetting and Swelling Of Pvp-gfms Plma And Pvp/pl...mentioning
confidence: 99%
“…While this study sorted all NR positive particles as plastic, the use of different fluorescence and size characteristics within a natural particle sample as sorting criteria could further separate plastics from other types of particles. It could also enable sorting focused on specific plastic polymers or polymer aging characteristics, based upon differing fluorescence characteristics (Maes et al 2017;Tigner et al 2023); these chemical features could then be confirmed by PyGCMS or microRaman. Forward and side scatter in FCM could be used to isolate specific particle morphologies, confirmed with fluorescence microscopy.…”
Section: Comments and Recommendationsmentioning
confidence: 99%